HAK DAN KEWAJIBAN ANAK ANGKAT - Fajarwati (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2024)
Islamic law prohibits the practice of adopting children which has juridical implications such as adoption which is known by western law/secular law and the practice of jahiliyah society: namely adoption which makes adopted children become biological children, adopted children are cut off from legal relations with their biological parents, adopted children have Inheritance rights are the same as the inheritance rights of biological children, adoptive parents become absolute guardians of adopted children. Islamic law only recognizes adoption in the sense of transferring the obligation to provide daily living, education, care and so on, in the context of worshiping Allah.